Half the church : recapturing God's global vision for women - James, Carolyn Custis, 1948- (Grand Rapids, Mich. : Zondervan, 2011)
Carolyn Custis James unpacks three transformative themes the Bible presents that invest the lives of every woman and girl with cosmic significance that nothing can destroy. These new images of what can be in Christ come with a blazing call for them to join their brothers in advancing God's gracious kingdom on earth. Carolyn offers readers a positive, kingdom approach to the changes, challenges, and opportunities facing women throughout the world today. --from publisher description.
Going global -- Identity theft -- Bearing God's image in a broken world -- The shaping of a leader's soul -- The ezer unbound -- Here comes the bride! -- The blessed alliance -- The great debate -- Waking the sleeping giantess.
Includes bibliographical references.
Keywords: Women in Christianity; Women and religion